2016
DOI: 10.1136/oemed-2016-103774
|View full text |Cite
|
Sign up to set email alerts
|

Mediating pathways and gender differences between shift work and subjective cognitive function

Abstract: Occupational health and safety programmes are needed to address stress and health factors, in addition to sleep hygiene, to effectively address cognitive function among shift workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…A recent path-modeling study reported job strain, which includes performance pace and intensity of work-related demands, to be a significant mediator of the relationship between shift schedules and sleep quality. Compared to day shift only employees, job strain was higher among permanent night and rotating shift workers, and this was significantly and indirectly associated with compromised sleep quality38 ) .…”
Section: Workplace Psychosocial Factorsmentioning
confidence: 99%
“…A recent path-modeling study reported job strain, which includes performance pace and intensity of work-related demands, to be a significant mediator of the relationship between shift schedules and sleep quality. Compared to day shift only employees, job strain was higher among permanent night and rotating shift workers, and this was significantly and indirectly associated with compromised sleep quality38 ) .…”
Section: Workplace Psychosocial Factorsmentioning
confidence: 99%
“…To our knowledge, this is the first Canadian study confirming this association in a very large, representative, population-based sample using objective cognitive measures. Given that cognitive processes are regulated by the circadian rhythm [ 6 , 7 ], misaligned circadian rhythm may represent one of the potential mechanisms explaining this relationship. As shiftwork takes place outside regular daytime working hours, working against the natural sleep–wake cycle may disrupt the circadian rhythm, resulting in impaired cognition in the long term [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shiftwork is associated with sleep loss [ 4 ] and the development of numerous health conditions which may be a product of disrupted circadian rhythms due to abnormal work hours [ 5 ]. As cognitive processes are regulated by the endogenous circadian clock [ 6 , 7 ], shiftwork may impair cognitive functioning as well [ 8 ]. Shiftwork has also been found to share common risk factors for cognitive impairment, including higher risks of social isolation, being overweight, and unhealthy lifestyles including smoking [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations